Improving biliary stent patency by the use of stent coating – a prospective randomized porcine study - Weickert, U.; Weddeling, S.; Subkowski, T.; Eickhoff, A.; Reiss, G. (Zeitschrift für Gastroenterologie, 2016)
Background: Endoscopic stenting of the bile duct is a standard procedure for almost 35 years. In the case of long-term stenting occlusion of the stent is a major concern. Therefore optimizing biliary stents with respect to their patency is of great importance. We tested in an in animal study if coating of self-expanding metal stents with hydrophobin alone or hydrophobin with heparin reduces stent clogging as there were promising results in an in vitro study with this approach.Material and methods: In a randomized prospective animal study we implanted self-expanding metal stents either native or coated with hydrophobin alone or coated with hydrophobin and heparin into the bile duct of 15 pigs. After a survival period of 6 weeks we measured which part of the stent surface (%) was covered with clogging material using a commercially available image editing program on scanning electron microscopic images.Results: We found no differences between the native self-expanding metals stents and those coated with hydrophobin alone or hydrophobin and heparin.Conclusion: There are important differences in the clogging process between in vitro and in vivo models. Coating with hydrophobin with or without heparin is not able to inhibit the clogging process in an animal model.
Keywords: Gallengangsstents; Nanotechnologie; Rasterelektronenmikroskopie